The influence of sex on lower limb biomechanical characteristics during single-leg drop landing in individuals with unilateral functional ankle instability - Cui, Huizi; Wang, Zilong; Lin, Minjie; Liu, Tao; Wang, Xiangdong (Frontiers in Bioengineering and Biotechnology, 2025)
ObjectiveTo investigate sex differences in lower limb biomechanics during single-leg drop landing in individuals with unilateral Functional Ankle Instability (FAI).MethodsTwenty individuals with unilateral FAI (10 males/10 females) performed single-leg drop landings on unstable and stable limbs respectively. Kinematic data were captured using a Vicon motion capture system, and kinetic data were collected using force plates. Data were analyzed using a 2 × 2 (Sex × Side) mixed-design ANOVA.ResultsSignificant main effects of Sex were observed for hip flexion and abduction angles at both IC and peak vGRF, with females showing greater hip flexion (p = 0.005; p = 0.023) and smaller hip abduction (p = 0.026; p = 0.003) than males. A significant main effect of Sex was also found for ankle inversion at IC, with females exhibiting greater inversion than males (p = 0.005). For ankle plantarflexion at IC, a significant Sex × Side interaction was detected (p = 0.020); simple effects analysis revealed that females had reduced plantarflexion on the unstable side compared to their stable side (p = 0.010). For peak vGRF, a significant Sex × Side interaction was observed (p = 0.013); post hoc tests indicated that females had higher peak vGRF on the unstable side than males (p = 0.008) and their own stable side (p < 0.001). No significant differences were observed for knee joint angles, T_vGRF, LR, ΔL, or Kleg (p > 0.05).ConclusionFemale individuals with FAI employ a hip-dominant compensatory strategy (increased flexion/reduced abduction) and exhibit greater ankle inversion than males. On the unstable side, they demonstrate reduced plantarflexion compared to their stable side. Males with FAI primarily adopt a joint stiffening strategy with restricted motion. Future research on FAI should incorporate sex differentiation in biomechanical assessments to develop targeted rehabilitation.